Grammatical SLI: a distinct subtype of developmental language impairment? - Bishop, D; Bright, P; James, C; Bishop, S; Van der Lely, H (Cambridge University Press, 2000)
Eighteen children with specific language impairment (SLI), from 6 to 8 years of age, were compared with 9 control children matched on age and nonverbal ability (CA controls) and with 9 younger control children of comparable language level (LA controls). Half of the SLI group were rated on a teacher checklist as having pragmatic difficulties: these were referred to as the pragmatic language impairment (PLI) group; the remainder were the typical (SLI-T) group. Children’s responses to adult soliciting utterances were compared. All children usually responded to conversational solicitations, but children in the PLI group were more likely than control children to give no response, and they also made very little use of nonverbal responses, such as nodding. Nonverbal responding was closely related to the quality of children’s responses. Children who failed to use nonverbal responses also had a relatively high level of pragmatically inappropriate responses that were not readily accounted for in terms of limited grammar or vocabulary. This study lends support to the notion that there is a subset of the language-impaired population who have broader communicative impairments, extending beyond basic difficulties in mastering language form, reflecting difficulty in responding to and expressing communicative intents. The analytic methods developed for this project have promise for the study of pragmatic difficulties in other clinical groups.